The Global financial crisis and the developing world : transmission channels and fall-outs for industrial development - Nissanke, Machiko (UNIDO ViennaAT, 2010)
Evaluates the effects of the on-going global financial crisis on the developing world, focussing particularly on possible implications for its industries and welfare.